Zoology in Forensic Science: Unraveling Mysteries through Animal Clues - Shubham Sah; Neelabh Datta; Deepa Kumari (International Journal of Toxins and Toxics, 2024)
Traditionally, forensic wisdom has been grounded on mortal substantiation similar as fingerprints, DNA, and bloodstains to unravel the riddle of crimes. There's important untapped eventuality in the beast area that could unravel mystifications and bring culprits to justice. This composition explores the instigative area of crossroad of zoology and forensic wisdom by demonstrating how suggestions from creatures can be significantly contributed to felonious examinations. From beast poisons in analysis to DNA that gives suggestions on ancient living surroundings, the kind of material zoological substantiation provides is unmatched. Beast actions, commerce, and adaption can help restore your crime scene, identify suspects, and occasionally place death hour. For illustration, the presence of some species of insects on a dead body may give veritably useful information about the posthumous interval, while analysis of beast hair or fur can link a suspect to a crime scene. also, zoology can explain crimes involving wildlife trafficking, coddling, and beast atrocity. Through assaying the remaining cadavers of creatures, DNA samples, and trade records, there will be traceability of the origin of wildlife products, and the identification of those perpetrators shamefaced responsible for the same, latterly their separate felonious networks will get intruded. The work can open lookouts for multidisciplinary approaches, revise the study of crime, and the disquisition methodology, introducing new borders in a pursuit of justice, as well as environmental and ecological preservation. As wisdom advances and understanding the beast area grows, zoology in forensic wisdom has much lesser compass and will give a distinct tool for working crimes and guarding both mortal beings and wildlife.
Keywords: DNA Analysis; Ecological Preservation; Forensic science; Wildlife Trafficking; Zoology